2019
DOI: 10.1088/1742-6596/1360/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Learning Management System (LMS) schoology: Why it’s important and what it looks like

Abstract: E-learning becomes one of the concepts deriving learning management system (LMS) which is designed to identify the gaps in teaching learning process, analyzing and reporting the data received automatically. One of the upgrading platforms of this learning management system recently is Schoology. It serves collaborative blended learning units which is form used in revolution 4.0 era. In investigating the reason of why Schoology is important and try to dig more information of its look, interview and documentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 5 publications
1
17
0
3
Order By: Relevance
“…Besides, using Schoology can also be managed everywhere without bringing the test in class with the teacher. This finding was confirmed by the previous research that Schoology as an online learning platform is flexible, fun-featured, easy-touse for creating, sharing, and submitting academic assignments (Ferdianto & Dwiniasih, 2019). In this case, one of Schoology's good features is practical and flexible, which can save users time.…”
Section: A Efl Students' Perception Of Blended Learning Via Schoologysupporting
confidence: 79%
“…Besides, using Schoology can also be managed everywhere without bringing the test in class with the teacher. This finding was confirmed by the previous research that Schoology as an online learning platform is flexible, fun-featured, easy-touse for creating, sharing, and submitting academic assignments (Ferdianto & Dwiniasih, 2019). In this case, one of Schoology's good features is practical and flexible, which can save users time.…”
Section: A Efl Students' Perception Of Blended Learning Via Schoologysupporting
confidence: 79%
“…Research was conducted by Ferdianto and Dwiniasih [24] in 2019 showed the visualization of Schoology as a platform that can be used in online learning. Schoology consist of four features, such as: features of tests and quizzes, features of content delivery, features of video viewing/link sources, and features of discussion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research was conducted by Ekici [27] in 2017 showed the use of Edmodo as a platform that can be used to create online communities in the learning process. Research by Ferdianto and Dwiniasih [24]; Gunawan et al [25]; Mulyono [26]; and Ekici [27]; strengthening the foundation for the author to conducted research more deeply on the selection of priority platforms used to support the learning process during social distancing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a tool for organizing distance learning by (Kerimbayev et al, [1] . As state by Ferdianto and Dwinasih, [2]. Schoology is one of the widely used Learning Management Systems (LMS) that can use in the teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%